OP09 Impacts of post-brexit agricultural policy on fruit and vegetable intake and cardiovascular disease in england: a modelling analysis. (3rd September 2019) - Seferidi, P; Laverty, AA; Pearson-Stuttard, J; Collins, B; Bandosz, P; Capewell, S; O'Flaherty, M; Millett, C
Abstract : Background: Brexit might produce a new agricultural regime in the UK. The current Agriculture Bill, which will shape this regime, aims to provide financial assistance for the delivery of environmental aims. However, the current Bill may represent a missed opportunity to positively influence food systems and improve public health. Potential health-improving measures could include expanding the UK production of fruits and vegetables (F&V), thus increasing F&V availability and affordability. Currently, only 1.4% of total agricultural land in England is allocated to F&V. This study aims to estimate the potential impacts of allocating additional land to F&V production on F&V intake and associated cardiovascular disease (CVD) and inequalities in England between 2021 and 2030. Methods: We used the previously validated IMPACT Food Policy model. We translated changes in land allocated to F&V into changes in F&V intake and associated CVD mortality, expressed in number of deaths prevented or postponed by age group, sex, and Index of Multiple Deprivation (IMD) quintile. The model combined publicly available data on agricultural land use and quality, F&V supply, waste, purchases and IMD-stratified intake, IMD-stratified CVD projections, and appropriate relative risks. We modelled two scenarios that assumed a linear increase in agricultural land allocated to F&V between 2021 and 2027 (the implementation period of the new policy) until it covers (a) 10% and (b) 20% of all high quality land suitable for production of horticultural crops in England. We assumed that F&V prices would drop to a new market equilibrium. We used Monte-Carlo simulations to produce uncertainty intervals. Results: Our model suggested that by 2030, fruit intake might increase by approximately 4% (95% Uncertainty Interval: 2%-7%) and vegetable intake by approximately 8% (4%-13%) under the first scenario. Under the second scenario, fruit intake could increase by approximately 17% (10%-29%) and vegetable intake by approximately 37% (26%-51%). These increases in F&V intake might prevent or postpone approximately 3, 360 (1, 760–5, 920) CVD deaths under the first scenario and 15, 700 (9, 000–24, 310) CVD deaths under the second scenario, between 2021 and 2030. Our modelled scenarios could also reduce inequalities, with some 16% of these fewer deaths occurring in the most affluent group compared with 22% in the most deprived group. Conclusion: Policymakers should urgently consider the public health impacts of the post-Brexit agricultural regime in England. Increasing the land allocated to F&V production could substantially reduce the burden of CVD and associated inequalities.